HISTO-CHEMICAL CHARACTERISTICS OF THE OVARIES OF CATTLE GROWN IN THE RADIOACTIVE CONTAMINATED AREA - Zaika, S. S.; Kot, T. F.; Guralska, S. V.; Sokulskiy, I. M.; Khomenko, Z. V. (Scientific Progress & Innovations, 2019)
The stay of animals on the territory polluted by radionuclides, feeding with forages of local origin expos-es their organism to constant external and internal irradiation. In this regard, an extremely important prob-lem of veterinary medicine is studying the effect of ionizing radiation on animals. The aim of our research is to study chemical statistics and ovarian dynamics: the location and nature of the reaction to the content of nucleic acids, proteins, lipids in cattle, which was born and constantly kept in the zone of low-intensity ioniz-ing irradiation. Annually, the detailed information is given as to the analysis of histo-chemical detecting DNA and RNA in the organ histo-structure and functional activity of the animal ovaries as endocrine glands. The results of our histo-chemical studies of histological preparations, dyed by Brachet method, indicate a significant difference in the localization and placement of nucleic acids in the tissues of the ovaries cortical substance and loose fibrous connective tissue. The walls of blood vessels and primordial follicles have the highest concentration of nucleoproteins. The increase in the intensity of histo-chemical reactions in cells to the content of RNA coincides with the accumulation of protein substances in them, that is, factors affecting the nature of their metabolism caused by changes in the metabolic processes of RNA. The distribution of “common” proteins in the ovaries is not uniform. Most of them are concentrated in the follicle walls and connective stroma, where collagen and elastic fibers are close enough to each other. The dynamics of lipid content in the cells of the granular layer of normal and atretic ovarian follicles is of great interest, because there is a certain correlation between the level of lipids and the intensity of steroid excretion. In the basal layer of follicular epithelium of follicles, extremely pronounced sudanophilia was observed. At the same time, in large follicles that are capable of ovulation, it is almost absent. Characterizing the function of the ovaries as the organs of reproductive system and endocrine glands, it can be affirmed that they regulate and affect complex cyclic neuro-humoral processes in the organism, which are confirmed by histo-chemical ex-amination. At the same time, histo-chemical changes occurring in them depend on the animal age and the functional state of the organism.